Linoleate-pazopanib conjugation as active pharmacological ingredient to abolish hepatocellular carcinoma growth - Wang, Ke; Liao, Pei-Yin; Chang, Wei-Chun; Yang, Cian-Ru; Su, Yu-Ting; Wu, Ping-Ching; Wu, Yang-Chang; Hung, Yao-Ching; Akhtar, Najim; Lai, Hsueh-Chou; Ma, Wen-Lung (Frontiers in Pharmacology, 2024)
Small molecule compounds targeting multiple kinases involved in neoangiogenesis have shown survival benefits in patients with unresectable hepatocellular carcinoma (HCC). Nonetheless, despite the beneficial effects of multikinase inhibitors (MKIs), a lack of boosting adjuvant limits their objective response rate. Lipid conjugates have been used to improve delivery efficacy or pharmaceutical benefits for decades. However, the feasibility of utilizing lipid-drug conjugates (LDCs) in HCC regimens remains untested. In this study, oral feeding of linoleate-fluorescein isothiocyanate conjugates showed 已刪除: es